INFLUENCE PREMIUM, RESULTS INVESTMENT AND LIABILITIES TO GROWTH ASSETS ON COMPANY SEA INSURE - Humaemah, Ratu; Syahputri, Mia Aryani; Darmawansyah, Trisna Taufik (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Growth asset company seainsure experience fluctuation data finance quarterly. From data increased asset growth There are factors that cause assets to increase and decrease, Wrong One factor Which influential to growth asset company insurance seainsure is premium income, investment returns, and liabilities. The method used in this research is regression multiple linear and classical assumption tests, to find out the results of data processing this company uses SPSS software. Based on Sea Insure's quarterly financial reports from 2019 to 2023, This research aims to determine independent variables such as premiums, investment returns and liabilities whether it has a positive impact or not on the company's growth. Samples used all over population of quarterly financial reports of seainsure companies from 2019 to 2023 which were accessed via https://seainsure.co.id . The results of this research show that simultaneously the variables independent (premium, results investment And liabilities) influential significant to level growth asset in the seainsure company with the significance value of the F test results obtained calculated f = 93.635 with value significant = 0.000 < 0.05. Premiums on investment returns and liabilities have a significant effect due to premiums is the main source of income used to increase company assets. Investment from premium generate profits that increase assets. Payment Obligations Payment of claims and obligations others reduce assets, so good liability management is essential to maintain growth asset.